Chinese normative values of C1 sagittal canal diameter and definition of C1 hypoplasia. Issue 11 (5th June 2021) - Wang, Yang; An, Yan; Tian, Wei; Ma, Yi-Min
Abstract : Supplemental Digital Content is available in the text